Effect of hot press sintering parameters on microstructure and mechanical properties of Ti35421 - JIA Guorong; LU Leiyi; MIN Jin; CAO Xihao; GUO Yanhua; SUN Zhonggang; CHANG Hui (Fenmo yejin jishu)
The Ti‒3Al‒5Mo‒4Cr‒2Zr‒1Fe (Ti-35421, mass fraction) titanium alloys were prepared by hot pressing sintering in this paper. The influences of sintering temperature, sintering pressure, and holding time on the microstructure and mechanical properties of Ti-35421 alloys were explored by orthogonal experiments and characterized by relative density, secondary α phase dimension, hardness, and compression properties. The results show that the sintering temperature is the most important parameter affecting the properties of Ti-35421 alloys. As the sintering temperature increases, the yield strength first increases and then decreases, the fracture strain first decreases and then becomes stable. At the same time, the high sintering temperature causes the grain growth, which reduces the compressive properties of the Ti-35421 alloys. The optimal sintering parameters are followed as the temperature of 900 ℃, the sintering pressure of 45 MPa, and the sintering time of 2 h, and the corresponding yield strength and fracture strain of the Ti-35421 alloys reach 1248 MPa and 23.03%, respectively. The Ti-35421 alloys obtained by hot pressing sintering are mainly composed of the original β grains and secondary α phase within the grains. As the sintering temperature increases, the size of β grains in the sintered body increases significantly, and the aspect ratio of the secondary α phase also increases.